Pengembangan Sistem Informasi Penilaian dan Evaluasi Kinerja Karyawan Dengan Metode Weighted Product Berbasis Web (Studi Kasus: UB Guest House) - Brendy Oscar Munthe; Faizatul Amalia; Imam Cholissodin (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Employee performance assessment and evaluation at UB Guest House is used to determine the level of employee performance achievement. The assessment process is still done manually starting from the preparation of forms, assessing employees, calculating the results by each assessor who can provide opportunities for miscalculation, recapitulation in making reports to determine the best employees only done for 3 days Timelines that are not proportional to work and the possibility of red dates result in no re-checking so that they do not exceed the set time limit. The assessment report is used to find out the progress every month to be evaluated together with the Employee Performance Evaluation Form to make employee awards. This is inefficient because it makes it difficult to choose employees to evaluate and discard paper that supports the UB Guest House costs. A web-based employee performance assessment and evaluation information system was built to overcome these problems. System development applies the weighted product method used to provide recommendations in determining the best employees and is carried out using a waterfall development model. Unit tests show that cyclomatic complexity â‰¤ 10 with all test case statuses is valid. Integration testing obtained for all test case statuses is valid. Validation testing obtained valid status for all test cases. Testing accuracy using the weighted product method obtained an accuracy of an average of 92%. System compatibility tests are obtained which can be run on various browsers.